Long term but not short term exposure to obesity related microbiota promotes host insulin resistance. Issue 1 (December 2018) - Foley, Kevin; Zlitni, Soumaya; Denou, Emmanuel; Duggan, Brittany; Chan, Rebecca; Stearns, Jennifer; Schertzer, Jonathan
Abstract The intestinal microbiota and insulin sensitivity are rapidly altered after ingestion of obesogenic diets. We find that changes in the composition of the fecal microbiota precede changes in glucose tolerance when mice are fed obesogenic, low fiber, high fat diets (HFDs). Antibiotics alter glycemia during the first week of certain HFDs, but antibiotics show a more robust improvement in glycemic control in mice with protracted obesity caused by long-term feeding of multiple HFDs. Microbiota transmissible dysglycemia and glucose intolerance only occur when germ-free mice are exposed to obesity-related microbes for more than 45 days. We find that sufficient host exposure time to microbiota derived from HFD-fed mice allows microbial factors to contribute to insulin resistance, independently from increased adiposity in mice. Our results are consistent with intestinal microbiota contributing to chronic insulin resistance and dysglycemia during prolonged obesity, despite rapid diet-induced changes in the taxonomic composition of the fecal microbiota. Gut microbiota impact host metabolism and gut microbiome composition reflects dietary habits. Here the authors show that, in animals fed obesogenic diets, changes in gut microbiota precede changes in glucose homeostasis. Importantly, long term exposure of the host to the changed microbiota is required to impair glucose homeostasis.